MORBILI PADA ANAK DALAM PENGOBATAN ANTI RETRO VIRAL (ARV) - Surya Dipta Nugraha (DiscoverSys Inc., 2015)
Introduction: Morbili is an acute viral infectious disease caused by a virus transmitted morbili. Morbili is a contagious acute viral infectious disease that is characterized by three stages: catarrhal stage, eruption stage and convalence stage. Another name morbili is measles, measles, or rubeola. Morbili caused by a virus that is classified as Family paramyxovirus, the virus genus morbili contained in nasopharyngeal secretions and blood during the prodromal period until 24 hours after the onset of spots.Case: Patient male, 6 years old, Hindu, Balinese tribe, came with complaints of febris since 5 days ago. Febris is not measured with a thermometer. The heat is felt up and down, getting better with medicine. Complaints red spots felt since 1 day ago. Originally discovered red spots appear in the neck area and then to the face and chest. The incidence of rash accompanied by itching and heat. This complaint is accompanied with nosebleeds 1 day ago, cough with sputum since 5 days ago and the red eye from one day ago. Patients feel the first time such complaints. Having a history of antiretroviral use regularly since 1.5 years old.